2012
DOI: 10.1200/jco.2011.37.2649
|View full text |Cite
|
Sign up to set email alerts
|

Elotuzumab in Combination With Lenalidomide and Low-Dose Dexamethasone in Relapsed or Refractory Multiple Myeloma

Abstract: The combination of elotuzumab, lenalidomide, and low-dose dexamethasone was generally well tolerated and showed encouraging response rates in patients with relapsed or refractory MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
183
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(191 citation statements)
references
References 16 publications
1
183
0
4
Order By: Relevance
“…20 The premedication regimen and administration schedule of these medications implemented in studies 1703 and 009 were shown to successfully reduce the number and severity of IRs associated with elotuzumab. 19,22 As a result, this premedication regimen, or an appropriate equivalent, is currently required for all patients prior to infusion of elotuzumab. In the ELOQUENT-2 study, patients received the premedication regimen that had been developed during study 1703.…”
Section: Introductionmentioning
confidence: 99%
“…20 The premedication regimen and administration schedule of these medications implemented in studies 1703 and 009 were shown to successfully reduce the number and severity of IRs associated with elotuzumab. 19,22 As a result, this premedication regimen, or an appropriate equivalent, is currently required for all patients prior to infusion of elotuzumab. In the ELOQUENT-2 study, patients received the premedication regimen that had been developed during study 1703.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, two of 28 treated patients experienced grade 3-4 allergic reactions during elotuzumab first cycle. [23] Those preliminary data supported a randomized phase III trial, which was recently completed. Six hundred and forty-six patients from 168 sites were randomly assigned to receive either elotuzumab, lenalidomide, and dexamethasone, or lenalidomide and dexamethasone.…”
Section: Treatment Of Post Auto-sct Relapsementioning
confidence: 83%
“…By comparison, the anti-CS1 mAb elotuzumab exhibited minimal single-agent activity, without objective responses in a Phase I doseescalation study [50] and has proven to be most promising in combinations with lenalidomide [51] and bortezomib [52]. Indeed, the degree of response observed with DARA at doses of 4 mg/kg and higher is reminiscent of the antitumor activity noted in early studies of single-agent thalidomide (32% with at least a 25% reduction in serum or urine M-protein) [53], lenalidomide (rate of MR or better, 26%) [54] and bortezomib (rate of PR or better, 38%) [55].…”
Section: Expert Opinionmentioning
confidence: 99%